2017
DOI: 10.1074/jbc.m116.758888
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between the glucocorticoid receptor and MyoD family inhibitor domain-containing protein provides a new mechanism for generating tissue-specific responses to glucocorticoids

Abstract: Glucocorticoids are primary stress hormones that regulate many physiological processes, and synthetic derivatives of these molecules are widely used in the clinic. The molecular factors that govern tissue specificity of glucocorticoids, however, are poorly understood. The actions of glucocorticoids are mediated by the glucocorticoid receptor (GR). To discover new proteins that interact with GR and modulate its function, we performed a yeast two-hybrid assay. The MyoD family inhibitor domain-containing protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…Approximately 30 μg of total protein was resolved on a 4%–20% Tris-glycine gel (Bio-Rad) and transferred onto a 0.2 μM nitrocellulose membrane (Bio-Rad). Membranes were blocked with blocking buffer (LI-COR Biosciences, Lincoln, NE) and incubated overnight with either anti-GR 59 ( Oakley et al, 2017 ), anti-phosphoserine 211 GR (Cell Signaling Technology), anti-FSHR (Abcam), anti-hCGR (LHR, Abcam), or anti-β-actin (Millipore). Total GR, phosphorylated GR, FSHR, and LHR were used at 1:1,000, and β-actin was used at 1:10,000.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 30 μg of total protein was resolved on a 4%–20% Tris-glycine gel (Bio-Rad) and transferred onto a 0.2 μM nitrocellulose membrane (Bio-Rad). Membranes were blocked with blocking buffer (LI-COR Biosciences, Lincoln, NE) and incubated overnight with either anti-GR 59 ( Oakley et al, 2017 ), anti-phosphoserine 211 GR (Cell Signaling Technology), anti-FSHR (Abcam), anti-hCGR (LHR, Abcam), or anti-β-actin (Millipore). Total GR, phosphorylated GR, FSHR, and LHR were used at 1:1,000, and β-actin was used at 1:10,000.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, glucocorticoid resistance may also be acquired and localized to the sites of inflammation (169) with pathological conditions (224). Glucocorticoid sensitivity is largely determined by a number of factors including the intracellular density and distribution of glucocorticoid receptors (183), 11βHSD1-mediated intracellular synthesis of active cortisol from inactive cortisone (179), tissue-specific presence of coregulatory proteins, the phosphorylation status of GR, the sequence of the GR-binding site and flanking DNA on target genes (184,225), post-translational modifications of GR, the availability of specific co-activators and co-repressors, epigenetic regulators, the chromatin landscape (187,190), and cross-talk with MyoD family inhibitor domain-containing proteins (226).…”
Section: Glucocorticoid Sensitivitymentioning
confidence: 99%
“…Hence, MDFI and MDFIC may plausibly perform many functions unrelated to transcriptional coregulation on the chromatin, yet may affect some transcriptional regulators in the cytoplasm. And indeed, previous studies have shown that MDFIC binds to and affects the glucocorticoid receptor in the cytoplasm 13 , or that MDFI and MDFIC interact with the cytoplasmic AXIN1 protein and in this manner modulate levels of the transcriptional cofactor β-catenin 4 . It is as well conceivable that MDFI and MDFIC regulate JMJD1A activity in the cytoplasm, since this histone demethylase is also present to a large extent in the cytoplasm of colon cancer cells 19 where it may potentially demethylate cytoplasmic, non-histone proteins.…”
Section: Discussionmentioning
confidence: 96%
“…When cells were treated with glucocorticoid, this interaction dissolved and the receptor translocated into the cell nucleus while MDFIC stayed behind in the cytoplasm. Moreover, transcriptome analyses revealed that MDFIC can influence the inflammatory response mediated by the glucocorticoid receptor 13 . However, no Mdfic -/mouse model has yet been published that could corroborate these potential functions of MDFIC.…”
mentioning
confidence: 99%